Analisa Perbandingan Nilai Akurasi Exponential Smoothing dan Linier Regresion pada Peramalan Permintaan Part Joint Brake Rod KTMY - Samitha Pujia Khan; Wahyudin Wahyudin; Sekar Mustika Ayuningtyas; Wagiana Rohmah; Zaskya Indah Vindari; Adinda Gita Azzahra (Jurnal Serambi Engineering, 2023)
PT XYZ is a local company that produces Joint Brake Rod KTMY parts whose demand varies every month. The production planning used by the company is often not by the demand so there is an excess of product stock that can trigger losses for the company. This study aims to determine the optimal step in planning the production of Joint Brake Rod KTMY parts in 2022 by comparing the value of the error accuracy rate of the two forecasting methods is exponential smoothing with 0,2; 0,5; 0,9 α value and the linear regression method. Furthermore, the calculation of the error accuracy value with Mean Absolute Deviation (MAD), Mean Squared Error (MSE) and Mean Absolute Percentage Error (MAPE) to determine the best forecasting. This resulting study indicates that linear regression is the method with the smallest accuracy, with 341.278 MAD; 185,084 MSE; and 0.11 MAPE. So, in planning production for Joint Brake Rod KTMY parts during the future period, PT. XYZ can use linear regression.